Roles of the Checkpoint Sensor Clamp Rad9-Rad1-Hus1 (911)-Complex and the Clamp Loaders Rad17-RFC and Ctf18-RFC in Schizosaccharomyces pombe Telomere Maintenance - Khair, Lyne (2010)
While telomeres must provide mechanisms to prevent DNA repair and DNA damage checkpoint factors from fusing chromosome ends and causing permanent cell cycle arrest, these factors associate with functional telomeres and play critical roles in the maintenance of telomeres. Previous studies have established that Tel1 (ATM) and Rad3 (ATR) kinases play redundant but essential roles for telomere maintenance in fission yeast. In addition, the Rad9-Rad1-Hus1 (911) and Rad17-RFC complexes work downstream of Rad3 (ATR) in fission yeast telomere maintenance. Here, we investigated how 911, Rad17-RFC and another RFC-like complex Ctf18-RFC contribute to telomere maintenance in fission yeast cells lacking Tel1 and carrying a novel hypomorphic allele of rad3 (DBD-rad3), generated by the fusion between the DNA binding domain (DBD) of the fission yeast telomere capping protein Pot1 and Rad3. Our investigations have uncovered a surprising redundancy for Rad9 and Hus1 in allowing Rad1 to contribute to telomere maintenance in DBD-rad3 tel1Δ cells. In addition, we found that Rad17-RFC and Ctf18-RFC carry out redundant telomere maintenance functions in DBD-rad3 tel1Δ cells. Since checkpoint sensor proteins are highly conserved, genetic redundancies uncovered here may be relevant to telomere maintenance and detection of DNA damage in other eukaryotes.